2020
DOI: 10.3892/etm.2020.9311
|View full text |Cite
|
Sign up to set email alerts
|

Associated risk factors of lower limb lymphedema after treatment of cervical and endometrial cancer

Abstract: The scope of the study was to identify the associated risk factors of lower limb lymphedema development in cervical and endometrial cancer patients. We retrospectively analysed 326 patients: 186 cases (57.06%) with cervical cancer and 140 cases (42.94%) with endometrial cancer were treated in Surgery, Radiotherapy, Oncology and Gynaecology Clinics of 'St. Apostle Andrew' Emergency Clinical Hospital Galati over 9 years. Adjuvant radiotherapy was performed in 83.57% of endometrial cancer cases. Adjuvant chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Biglia et al found that neither chemotherapy alone nor the association of consecutive chemotherapy and radiotherapy was associated with an increased incidence of lower limb lymphedema ( 13 ). In addition, there have been a few studies investigating the risk factors including BMI, nutritional status, number of removed lymph nodes, lymphedema, and adjuvant radiotherapy in patients having systematic lymphadenectomy ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biglia et al found that neither chemotherapy alone nor the association of consecutive chemotherapy and radiotherapy was associated with an increased incidence of lower limb lymphedema ( 13 ). In addition, there have been a few studies investigating the risk factors including BMI, nutritional status, number of removed lymph nodes, lymphedema, and adjuvant radiotherapy in patients having systematic lymphadenectomy ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…This surgical technique consists of parametrectomy and LN dissection. Accordingly, patients have a higher risk of postoperative complications, such as voiding difficulty ( 7 9 ), anorectal dysfunction ( 10 , 11 ), sexual dissatisfaction ( 10 , 11 ), and lymphedema ( 12 14 ), if parametrectomy or LN dissection becomes aggressive. Therefore, greater attention is being paid to minimally invasive surgery to minimize these postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…The main factors associated with secondary lower limb lymphedema are gynecological cancer, age, disease stage, radiotherapy, number of lymph nodes invaded (for patients with cervical cancer), number of lymph nodes removed (for patients with cervical cancer) and obesity, the most important of which are obesity and the number of lymph nodes removed [6].…”
Section: Introductionmentioning
confidence: 99%